2021
DOI: 10.1111/ejn.15126
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of endogenous glial cell line‐derived neurotrophic factor impairs spatial memory performance and raises inhibitory tone in the hippocampus

Abstract: Parvalbumin‐positive interneurons (PV+) are a key component of inhibitory networks in the brain and are known to modulate memory and learning by shaping network activity. The mechanisms of PV+ neuron generation and maintenance are not fully understood, yet current evidence suggests that signalling via the glial cell line‐derived neurotrophic factor (GDNF) receptor GFRα1 positively modulates the migration and differentiation of PV+ interneurons in the cortex. Whether GDNF also regulates PV+ cells in the hippoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Similarly, we observed a decline in Y-maze performance in old Gdnf wt/wt animals but interestingly not in old Gdnf wt/hyper mice. We recently found that young Gdnf wt/hyper mice have mildly impaired long-term memory in the Morris water maze test, accompanied by an increased number of PV + neurons and inhibitory tone in the hippocampus ( Marshall et al, 2021 ). However, Morris water maze test with old animals did not reveal differences between Gdnf wt/hyper mice and wild-type controls ( Turconi et al, 2020 ), suggesting a complex adaptation response that requires time to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we observed a decline in Y-maze performance in old Gdnf wt/wt animals but interestingly not in old Gdnf wt/hyper mice. We recently found that young Gdnf wt/hyper mice have mildly impaired long-term memory in the Morris water maze test, accompanied by an increased number of PV + neurons and inhibitory tone in the hippocampus ( Marshall et al, 2021 ). However, Morris water maze test with old animals did not reveal differences between Gdnf wt/hyper mice and wild-type controls ( Turconi et al, 2020 ), suggesting a complex adaptation response that requires time to be established.…”
Section: Discussionmentioning
confidence: 99%
“…NCAM1, integrins αv and β1, and N-cadherin induce neurite outgrowth, proliferation, survival, and influence axon guidance (Chao et al 2003 ; Paratcha et al 2003 ; Cao et al 2008 ; Zuo et al 2013 ; Ibáñez et al 2020 ) and several of these adhesion proteins may act as receptors for GDNF bound to its cognate receptor, GFRα1. Matrix-bound GDNF may also signal via Syndecan-3 (Bespalov et al 2011 ) which in turn affects GABAergic neuronal migration and is neither RET- nor NCAM-dependent (Pozas & Ibanez 2005 ; Canty et al 2009 ; Marshall et al 2021 ). Although RET and GFRα1 are expressed throughout development and adulthood in midbrain dopamine neurons, GFRα1 is expressed in the absense of RET in striatal neurons (Kramer & Liss 2015 ).…”
Section: Outside Gdnf-gfra1-retmentioning
confidence: 99%